Duress by Indirect Circumstances in English and South African Law: A Comparison – R v Brandford [2017] 2 All ER 43; [2016] EWCA Crim 1794 - Samantha Goosen (Obiter, 2021)
While duress by means of direct threats can provide a defence in criminal law, the legal question is whether threats conveyed indirectly are capable of providing a valid defence in criminal law. More specifically, can indirect threats then also be used as a means of defending another party’s interests that are under attack? There appears to be both academic support and precedent to answer this question in the affirmative.